Michelangelo - Stanley, Diane (New York : HarperCollins, 2001)
A biography of the Renaissance sculptor, painter, architect, and poet, well known for his work on the Sistine Chapel in Rome's St. Peter's Cathedral.
G11
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Juvenile literature; Michelangelo Buonarroti, -- 1475-1564.; Artists -- Italy -- Biography -- Juvenile literature; Artists